Trilogi Konflik Tanah Ulayat Pulurera di Flores Timur. - Umbu TW Pariangu; Benedicta Bean (Prodi Sosiologi FISIP Universitas Teuku Umar, 2021)
ABSTRACTLand conflicts in Indonesia occur in various forms such as land grabbing, unilateral claims, land border issues, and so on. In East Flores Regency (Flotim), East Nusa Tenggara, land conflicts always attract public attention, such as the conflict between PT. Rerolara with the Pulurera Village community in 2019. The conflict was triggered by the issue of the termination of the Hak Guna Usaha (HGU) contract and the abandonment of land by PT. Rerolara so that the people of Pululara Village claim the land is included in Pululara's ulayat rights. However, this action was opposed by PT. Rerolara and several tribes holding ulayat rights have triggered social instability which has led to civil war between residents. Conflicts in Pulurera Village are classified into three types (trilogy) of conflict: data conflicts, conflicts of interest, and relationship conflicts. Ironically again, a compromise point is difficult to create because the arena of conflict does not only involve institutions that are diametrically in conflict (PT Rerolara and the Tukan Tribe Village community) but several ethnic groups (in Boru Village, Nawokote Village) are also affiliated with PT Rerolara so that it seems that there is an intention legitimize the continuation of conflict and land ownership claims in the name of the community's sovereign rights. Keywords: conflict trilogy, customary land, local community, Rerolara, Ulayat